Researches on LINE Today as News Aggregator - Sofia Aunul; Daniel Handoko (Jurnal Visi Komunikasi, 2022)
News aggregator is as a process of taking news from published sources, then reshaping the news, and republishing it in a shorter form in one presentation. LINE today as news aggregator appeared on the third stage of the time line of online journalism in Indonesia. This paper attempts to highlight previous studies findings about LINE Today as news aggregator. News aggregator faces domino effect in which audiences think that news aggregator is not credible as a result of data mining gibing repetitive information. On the other hand, it is urgent that there should be encouragement of digital journalist competence to be familiar with aggregation. Later, this leads to the idea of slow technology as an antithesis of interactive technology (news aggregator) that is based on human-centered activity.